Influence of different irrigation methods and schedules on water productivity of wheat - SURYAVANSHI, P.; BUTTAR, G. S. (Journal of Soil and Water Conservation, 2021)
A field experiment was conducted at Punjab Agricultural University, Ludhiana to determine the most efficient irrigation methods and schedule for achieving higher water productivity in wheat during rabi 2013-14 and 2014-2015. The experiment was laid out in randomized complete block design keeping combinations of three irrigation methods (check basin, drip and sprinkler irrigation) and four irrigation schedules (CPE:IW 0.6, 0.8, 1.0 and 1.2) along with recommended surface irrigation (7.5 cm depth) as extra absolute control treatment. During 2013-14, grain yield recorded was the highest in drip irrigation (5.10 t ha-1) followed by check basin (4.90 t ha-1) and the lowest in sprinkler irrigation method (4.74 t ha-1). Among irrigation schedules, significantly higher grain yield was obtained when irrigation was applied at CPE:IW 0.6 (5.37 t ha-1) than that at 1.0 (4.89 t ha-1) and 1.2 (4.7 t ha-1). Results revealed that during 2013-14, water productivity of drip irrigated wheat (16.18 kg ha-1 mm-1) was significantly higher than sprinkler irrigated wheat (14.59 kg ha-1 cm-1) and check basin method (15.35 kg ha-1 mm-1). These results clearly demonstrated that irrigating wheat at 0.6 CPE/IW ratio using drip method of irrigation is a novel concept that saves irrigation water in addition to higher grain yield.